2013
DOI: 10.2217/bmt.13.16
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking pregnancy as a strategy for breast cancer prevention

Abstract: SUMMARY Pregnancy and its effects on breast cancer risk have been widely investigated; there is consensus among researchers that early pregnancy confers protection against breast cancer later in life, whereas nulliparity and late-age parity have been associated with increased risk of developing breast cancer. The answer to the question of how pregnancy reduces breast cancer risk has been elusive; however, pregnancy, like breast cancer, is a similar hormone-dependent entity under direct control of estrogen, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 69 publications
0
21
0
1
Order By: Relevance
“…Both pregnancy and breast cancer are hormone dependent conditions which are under direct influence of estrogen, progesterone and human chorionic gonadotropin (hCG) [28] Both hormonal and non-hormonal mechanisms have been suggested to explain the adverse effect of pregnancy on breast cancer risk [29]. The hormonal factors associated with pregnancy play a complex role in the occurrence of PABC along with a specific genetic background [30].…”
Section: The Effect Of Gestational Hormones On Breast Carcinogenesismentioning
confidence: 99%
“…Both pregnancy and breast cancer are hormone dependent conditions which are under direct influence of estrogen, progesterone and human chorionic gonadotropin (hCG) [28] Both hormonal and non-hormonal mechanisms have been suggested to explain the adverse effect of pregnancy on breast cancer risk [29]. The hormonal factors associated with pregnancy play a complex role in the occurrence of PABC along with a specific genetic background [30].…”
Section: The Effect Of Gestational Hormones On Breast Carcinogenesismentioning
confidence: 99%
“…Several studies found IGF1 expression to be decreased with parity (48, 9092). In a rodent model, circulating GH was reduced in parous animals leading to a reduction in mammary gland activation of the IGF/GH axis (13, 93).…”
Section: A Role For Insulin-like Growth Factor I In the Protective Efmentioning
confidence: 99%
“…Secondly, a possible avenue of prevention emerges: if a hormonally mimicked sham pregnancy can be induced, and a limited time of pseudo-lactation could be endured, childless women may be able to achieve the same reduced risk as young mothers [8]: the authors describe in their recent review the main changes in morphology and gene expression levels of the mammary gland of Sprague-Dawley rats exposed to known cancer-preventative conditions (pregnancy, human chorionic gonadotropin (hCG) and progesterone + estrogen). In addition, they postulate a protective mechanism induced by hCG that could reduce the cells' potential to be transformed by carcinogens.…”
Section: The Person At Risk As a Product Of Procreation (Prenatal Life)mentioning
confidence: 99%